Approaches to Comprehensive Performance Evaluation of Software Applications: A Systematic Literature Review - Unuchak, Yauhen; Unuchak, Tatyana (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Performance evaluation of modern software applications is necessary to optimize resources and improve the reliability of software applications, whose main problems are related to low throughput, long response times, and high support costs. Software Performance Engineering methodology provides early prediction and optimization using simulation, benchmarks and profiling. Analysis of publications revealed problems with data processing, lack of standardization of metrics and lack of effective application of analytical models, which complicate the process of evaluating the performance of information systems. Addressing these issues and standardizing approaches will help improve the processes for evaluating the performance and reliability of information systems that meet user and customer requirements.